Critiques of Serbian Civil Code of 1844 with Special Reference to Provisons on Zadruga - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Critiques of Serbian Civil Code of 1844 were presented in this paper. Namely, Serbian Code was not an original work, but rather abridged version of Austrian Civil Code (Allgemeines Bürgerliches Gesetzbuch). Critics objected to author of the Code Jovan Hadžić that he took himself too much liberty in his redaction work, so that some provisions become unclear. Hadžić was also criticized for very difficult language and style of codification and sometimes inaccurate legal terminology. But mostly Hadžić was criticized for miscomprehension of the legal nature of so - called zadruga (extended family, common among South Slavs), product of customary law. The entire institute of zadruga was regulated rather superficially, so that sometimes it was considered as a legal entity and sometimes as a condominium. Therefore, critiques of the provisions on zadruga were particularly examined in this paper.